Estudio de mercado para la creación de un operador turístico en el cantón Babahoyo - Avilez Rodriguez, Angel Jefferson (2022)
Ecuador is known for its tourist potential due to its biodiversity and multiculturalism, places such as the Quilotoa lagoon, the Amazon jungle, national beaches are examples of the country's potential, likewise there is the commitment of Ecuadorians to risk undertake in national tourism. This research aims to analyze the feasibility for the creation of a tour operator in the city of Babahoyo, to carry out this study an exploratory and documentary research was used, with a mixed quantitative and qualitative approach. Surveys were conducted to the inhabitants of the city and interviews to the different travel agencies duly registered in the national registry of tourist establishments, which allowed identifying the offer and demand that the city has. It was established that the inhabitants of the city feel a great interest in knowing different places in the country and are willing to hire tourist intermediation, on the other hand the current offer by travel agencies in the city of Babahoyo was corroborated and an approach towards the sale and promotion of packages to international destinations could be evidenced. This case study concluded that there is a feasibility for the creation of a tour operator in the city of Babahoyo, identifying a great market opportunity for it.